2020
DOI: 10.1371/journal.pone.0243776
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum modern contraception utilization and its determinants in Ethiopia: A systematic review and meta-analysis

Abstract: Background Contraceptive use is the best and most cost-effective strategy to reduce feto-maternal adverse effects of short birth intervals. More than two-thirds of women in developing countries who do not want to conceive are not using contraception methods. Although there were various primary studies in different parts of the country, there is no nationally representative evidence on postpartum modern contraception utilization and its determinants in Ethiopia. Objective This review was aimed to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
4
6
0
Order By: Relevance
“…Women who had formal education were 2.6 times more likely to utilize modern contraceptives during postpartum period compared to women who did not have formal education. This finding is similar with a previously conducted systematic review and meta-analysis study in Ethiopia [ 11 ]. This might be due to the fact that the more educated women have better understanding of benefits of contraceptives during postpartum period and risks of shorter inter-pregnancy interval.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Women who had formal education were 2.6 times more likely to utilize modern contraceptives during postpartum period compared to women who did not have formal education. This finding is similar with a previously conducted systematic review and meta-analysis study in Ethiopia [ 11 ]. This might be due to the fact that the more educated women have better understanding of benefits of contraceptives during postpartum period and risks of shorter inter-pregnancy interval.…”
Section: Discussionsupporting
confidence: 93%
“…However, there is huge variability in the findings. Moreover, although there were previous attempts to do a systematic review and meta-analysis, they included few studies and largely focused on one region of Ethiopia, limiting their generalizability to the country as a whole [ 11 , 12 ]. In our review we tried to include primary studies conducted from all major regions in Ethiopia to address this limitation.…”
Section: Introductionmentioning
confidence: 99%
“…First, as the level of educational attainment increases postpartum women are likely to have a better understanding of the available health facilities and the benefits of fertility regulation [26]. Second, women who have been educated are more likely to visit a health facility and receive counseling or services on family planning and go on to use contraceptives timely, than those who have not been educated [27,28]. Studies elsewhere have revealed a similar pattern of relationship between educational level and contraceptive use during postpartum [23,29].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…In Ethiopia, the utilization of PPFP ranges from 10.3% to 80.3% [ 16 , 17 ]. Reports of two different systematic reviews and meta-analysis studies done in Ethiopia show that the pooled magnitude of the utilization of modern PPFP methods was 45.79% and 48.11% [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%